PENGABDIAN MASYARAKAT TENTANG PENINGKATAN PENGETAHUAN KESEHATAN GIGI DAN MULUT TERHADAP SISWA-SISWI DI SMAN KABUPATEN SUMENEP - Setiawan, Fery; Prakosa, Basma Rosandi; Khafid, Mohammad; Rahmawan, Dzanuar; Nurmalasari, Afrida; Irawan, Rudi (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2025)
Perception of oral hygiene has a major impact on life expectancy worldwide, but in middle-income countries it is a problem, where oral health problems in Indonesia affect as much as 57.6% of the population. A semi-experimental study was conducted on February 21, 2025 on students at SMAN 1, SMAN 2, and Pondok Pesantren Mathlabul Ulum Jambu in Sumenep Regency, East Java, Indonesia. The study method was carried out offline (face-to-face) using a mixture of presentation media (power point) and booklets. The socialization participants were divided into two parts: pre-socialization (pre-test) and post-socialization (post-test). The socialization participants were given questions to assess their knowledge and perceptions of oral health before and after the socialization. Participants' knowledge was classified as sufficient, moderate, and low in understanding oral hygiene before and after the socialization. The average score for participants before the socialization was 60.66, and after the socialization it was 86.71. These results were significantly different with a p-value of 0.000 using the Wilcoxon statistical test. These data show that there is a positive role for dentists in improving dental and oral health in the environment of high school students so that dentists can play an active role in encouraging patients to pay more attention to dental and oral health awareness, especially for SMAN 1 and 2 in Sumenep Regency, East Java.